Development of advanced NO[sub x] control concepts for coal-fired utility boiler - Evans, A.; Pont, J. N.; England, G.; Seeker, W. R. (Energy and Environmental Research Corporation, 1993)
Hybrid technologies for the reduction of NO[sub x] emissions from coal-fired utility boilers have shown the potential to offer greater levels of NO[sub x] control than the sum of the individual technologies, leading to more cost effective emissions control strategies. Energy and Environmental Research Corporation (EER) has developed a hybrid NO[sub x] control strategy involving two proprietary concepts which has the potential to meet the US Department of Energy's NO[sub x] reduction goal at a significant reduction in cost compared to existing technology. The process has been named CombiNO[sub x]. CombiNO[sub x] is an integration of three technologies: modified reburning, promoted selective noncatalytic reduction (SNCR) and methanol injection. These technologies are combined to achieve high levels of NO[sub x] emission reduction from coal-fired power plants equipped with S0[sub x] scrubbers. The first two steps, modified reburning and promoted SNCR are linked. It has been shown that performance of the SNCR agent is dependent upon local oxidation of CO. Reburning is used to generate the optimum amount of CO to promote the SNCR agent. Approximately 10 percent reburning is required, this represents half of that required for conventional reburning. If the reburn fuel is natural gas, the combination of reburning and SNCR may result in a significant cost savings over conventional reburning. The third step, injection of methanol into the flue gas, is used to oxidize NO to N0[sub 2] which may subsequently be removed in a wet scrubber. Pilot-scale tests performed at EER's 1 MMBtu/hr Boiler Simulation Facility (BSF) have demonstrated NO[sub x] reductions up to 92%. The program's next phase entails process scale-up to a 10 MMBtu/hr furnace also located at EER's Santa Anna test site.